The choreography process for the Badah Unda' dance - Salma Ismahiro; Frisca Monicasari; Maharani Laza Lestari (Yayasan Baru Haji Samsudin, 2024)
The Badah Unda’ dance is a dance resulting from the development of the Sangkan Siheh dance originating from Lahat, South Sumatera. This study aims to explain the choreographic process which consists of the exploration, improvisation, and formation stages. The research method used is a qualitative descriptive method by collecting data in the form of books, journals, articles and other sources. This dance was created from the results of the development of the Sangkan Siheh dance movement, where the exploration of the movement was expanded again by paying attention to the activities and work of the Lahat area community. The goal is that this dance can continue to be preserved and better know by the wider community